The Implementation of Children’s Rights in Correlation with Parental Rights in the Upbringing Process: the Polish Perspective - Bielecki, Marek (Children’s Rights in the Sustainable and Digital Environments: Exploring Opportunities and Challenges: Exploring Opportunities and Challenges, 2025)
The subject matter of the present study is the examination of children's rights in correlation with parents' rights in the upbringing process. As it is assumed, the right of the parents to raise their children in accordance with their convictions belongs to the basic categories of rights that are guaranteed to parents and legal guardians at the normative level by the international community and the national legislator. The author analyses the current normative solutions in Poland from a national and international perspective. The first part of the study explains the basic concepts, i.e., family, upbringing, child or convictions. The second part presents the basic normative solutions applicable in the area of parental authority, education, and the rights to which a child is entitled. The whole study ends with a summary presenting conclusions of the analysis of the discussed issues.